2008
DOI: 10.1007/s00418-008-0468-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of prolyl oligopeptidase in the mouse whole-body sections and peripheral tissues

Abstract: Prolyl oligopeptidase (POP) is a serine endopeptidase that hydrolyses proline-containing peptides shorter than 30-mer, including many bioactive peptides. The distribution of POP in the brain has been studied but little is known about the distribution of peripheral POP. We used immunohistochemistry to localize POP in mouse wholebody sections and at the cellular level in peripheral tissues. Furthermore, we used a POP activity assay to reveal the associations between POP protein and its enzymatic activity. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 51 publications
(84 reference statements)
3
59
0
Order By: Relevance
“…In humans and rodents it is highly expressed in the brain (2), including the cortex, striatum, hypothalamus, hippocampus, and amygdala (3)(4)(5)(6). The physiological role of PREP remains elusive (7).…”
Section: Hypothalamic Prolyl Endopeptidase (Prep) Regulates Pancreatimentioning
confidence: 99%
“…In humans and rodents it is highly expressed in the brain (2), including the cortex, striatum, hypothalamus, hippocampus, and amygdala (3)(4)(5)(6). The physiological role of PREP remains elusive (7).…”
Section: Hypothalamic Prolyl Endopeptidase (Prep) Regulates Pancreatimentioning
confidence: 99%
“…PREP Activity Assay-PREP activity assay was used to confirm the enzymatic activity of various PREP constructs, and it was performed as described in Myöhänen et al (22,30). Briefly, the cells transfected with various PREP constructs were homogenized with lysis buffer (50 mM KH 2 PO 4 , 1.5 mM MgCl 2 , 10 mM NaCl, 1 mM EDTA, pH 7.4), and the homogenates were centrifuged at 16,000 ϫ g for 10 min at ϩ4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recent in vivo peptidomic studies have only partially confirmed potential endogenous substrates that were proposed by an in vitro investigation (Nolte et al 2009). Other biological functions correlated with its cytosolic localization (Dresdner et al 1982;Schulz et al 2002Schulz et al , 2005Venäläi-nen et al 2004;Myöhänen et al 2008) have been proposed, including the participation in inositol phosphate signaling (Williams et al 1999;Schulz et al 2002), protein secretion and/or axonal transport , and proteinprotein interaction (Di Daniel et al 2009). A study by Di Daniel et al (2009) has recently demonstrated that, in a PREP knockout primary neuronal culture, PREP is involved in the outgrowth of growth cones and that this action does not require its peptidase activity but a protein-protein interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The primary function of PREP is thought to hydrolyze the Pro-Xaa bond of short peptides (Polgar 1994;Cunningham and O'Connor 1997). In humans and rodents, it is highly expressed in several brain areas (Myöhänen et al 2008), including the hippocampus (Bellemère et al 2004). Several PREP inhibitors have been shown to improve memory impairment in animals (Schneider et al 2002) and they have been evaluated in preclinical trials as potential drugs for the treatment of the natural memory deficit that occurs with aging (Morain et al 2000) and the pathological memory loss characteristic of Alzheimer's disease (Mannisto et al 2007).…”
Section: Introductionmentioning
confidence: 99%